2009
DOI: 10.1186/1476-7120-7-24
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of exercise echocardiography in diabetic patients

Abstract: Background: Coronary artery disease (CAD) is the leading cause of death in diabetic patients. Although exercise echocardiography (EE) is established as a useful method for diagnosis and stratification of risk for CAD in the general population, there are few studies on its value as a prognostic tool in diabetic patients. The purpose of this investigation was to evaluate the value of EE in predicting cardiac events in diabetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The ESE also showed a significant prognostic value for late cardiac events in patients with atrial fibrillation, as demonstrated in the study by Poldermans et al 19 . A study by Oliveira et al 20 , with the objective to evaluate the prognostic value of ESE in patients with diabetes, showed that those with normal ESE had low rates of cardiac events in the first year after the examination.…”
Section: Discussionmentioning
confidence: 99%
“…The ESE also showed a significant prognostic value for late cardiac events in patients with atrial fibrillation, as demonstrated in the study by Poldermans et al 19 . A study by Oliveira et al 20 , with the objective to evaluate the prognostic value of ESE in patients with diabetes, showed that those with normal ESE had low rates of cardiac events in the first year after the examination.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetics with findings of ischemia on Exercise Echocardiography (EE) had worse cardiac outcomes compared to general population. Thereafter, EE could indeed be a tool for the prediction of adverse outcomes in diabetics with cardiovascular disease [ 47 ].…”
Section: Stress Echomentioning
confidence: 99%